Garcinia Mangostana Pericarp Extract Protection on Reproductive Function of Obese-Diabetic Rats Model - Nindita, Yora; Karlowee, Vega; Kesumayadi, Irfan; Istiadi, Hermawan; Muniroh, Muflihatul (Faculty of Medicine Universitas Padjadjaran, 2023)
Background: Type 2 diabetes mellitus (T2DM) in obese has been considered a risk factor for male infertility. Garcinia mangostana pericarp extract (GMPE) is known to have anti-hyperglycemic, anti-diabetic, and anti-inflammatory effects. This study aimed to evaluate the effect of GMPE therapy on reproductive function in obese T2DM rats by examining testosterone level, testicular histopathological features, and hs-CRP level.Methods: Thirty-six male Wistar rats, aged 2–3 months, were randomly divided into 6 groups and treated with a standard diet (NC), high-fat diet (HFD) with GMPE 200 mg/kgBW (obese GMPE control/OGC200), HFD with 45 mg/kgBW STZ-NA (obese-diabetic control/ODC), obese-diabetic rats with GMPE 100 (DG100); 200 (DG200); and 400 mg/kgBW (DG400). STZ-NA was administered after 8 weeks of HFD treatment and followed by GMPE for 8 weeks after T2DM was confirmed. The level of hs-CRP and testosterone were measured in the serum using an enzyme-linked immunosorbent assay. Testicular histopathological examination was measured after 8 weeks of treatment by using Modified Jonhson Score (MJS) with HE staining. Results: ODC rats significantly showed increased hs-CRP level compared to NC (8.76±0.27 vs 0.30±0.07 ng/mL, p<0.001) and reduced testosterone level and MJS compared to NC (73.69±2.22 vs 170.14±1.34 ng/dL, 4.57±0.93 vs 9.87±0.16 MJS, respectively, P<0.001). Testosterone and hs-CRP levels showed a negative and significant correlation (r=-0.974 and p<0.001). On the treatment group, GMPE significantly reduced hs-CRP and increased testosterone levels in a dose-dependent manner.Conclusion: GMPE effectively protects reproductive function in obese DM rats by increasing testosterone levels and advanced spermatogenesis, as well as decreasing hs-CRP level